Flavonoids for Treating Viral Acute Respiratory Tract Infections: A Systematic Review and Meta-Analysis of 30 Randomized Controlled Trials - Yao, Jia; Zhang, Yuan; Wang, Xian-Zhe; Zhao, Jia; Yang, Zhao-Jun; Lin, Yu-Ping; Sun, Lu; Lu, Qi-Yun; Fan, Guan-Jie (Frontiers in Public Health, 2022)
Background: This meta-analysis aimed to investigate the efficacy and safety of flavonoids in treating viral acute respiratory tract infections (ARTIs). Methods: Randomized controlled trials (RCTs) were entered into meta-analyses performed separately for each indication. Efficacy analyses were based on changes of disease-specific symptom scores. Safety was analyzed based on the pooled data from all eligible trials, by comparing the incidence of adverse events between flavonoids and the control. Results: Thirty RCTs (n=5166) were included. In common cold, results showed that the flavonoids group decreased total CIS, sum of SSID of CIS, and duration of inability to work versus the control group. In influenza, the flavonoids group improved the visual analogue scores for symptoms. In COVID-19, the flavonoids group decreased the time taken for alleviation of symptoms, time taken for SARS-CoV-2 RT-PCR clearance, the RT-PCR positive subjects at day 7, time to achievement of the normal status of symptoms, patients needed oxygen, patients hospitalized and requiring mechanical ventilation, patients in ICU, days of hospitalization, and mortality versus the control group. In acute non-streptococcal tonsillopharyngitis, the flavonoids group decreased the TSS on day 7. In acute rhinosinusitis, the flavonoids group decreased the SSS on day 7, days off work, and duration of illness. In acute bronchitis, the flavonoids group decreased the BSS on day 7, days-off work, and duration of illness. In bronchial pneumonia, the flavonoids group decreased the time to symptoms disappearance, the level of IL-6, IL-8, and TNF-α. In upper respiratory tract infections, the flavonoids group decreased total CIS on day 7 and increased the improvement rate of symptoms. Furthermore, results of the incidence of adverse reactions didn’t differ between the flavonoids and the control group. Conclusion: This systematic review and meta-analysis suggested flavonoids were efficacious and safe in treating viral ARTIs including common cold, influenza, COVID-19, acute non-streptococcal tonsillopharyngitis, acute rhinosinusitis, acute bronchitis, bronchial pneumonia, and upper respiratory tract infections. However, uncertainty remains because there were few RCTs per type of ARTI and many of the RCTs were small and of low quality with substantial risk of bias. We suggest the conclusions need to be confirmed in future studies.